2012
DOI: 10.1210/en.2012-1145
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Inhibits Human Androgen Production by Regulating Steroidogenic Enzymes HSD3B2 and CYP17A1 and Complex I Activity of the Respiratory Chain

Abstract: Metformin is treatment of choice for the metabolic consequences seen in polycystic ovary syndrome for its insulin-sensitizing and androgen-lowering properties. Yet, the mechanism of action remains unclear. Two potential targets for metformin regulating steroid and glucose metabolism are AMP-activated protein kinase (AMPK) signaling and the complex I of the mitochondrial respiratory chain. Androgen biosynthesis requires steroid enzymes 17α-Hydroxylase/17,20 lyase (CYP17A1) and 3β-hydroxysteroid dehydrogenase ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 56 publications
1
90
0
2
Order By: Relevance
“…Further, in one recent study, metformin lowered testosterone levels in women with PCOS despite the absence of any improvement in insulin sensitivity, as quantified by a frequently sampled IVGTT [40]. In vitro studies using cultured ovarian theca cells support a direct inhibitory effect of metformin on ovarian steroidogenesis [35,41,42] through inhibition of mitochondrial Complex I [35], a mechanism which has also been implicated in metformin action in the liver and other tissues [29,31].…”
Section: Impact Of Metformin On Reproductive Features Of Pcosmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, in one recent study, metformin lowered testosterone levels in women with PCOS despite the absence of any improvement in insulin sensitivity, as quantified by a frequently sampled IVGTT [40]. In vitro studies using cultured ovarian theca cells support a direct inhibitory effect of metformin on ovarian steroidogenesis [35,41,42] through inhibition of mitochondrial Complex I [35], a mechanism which has also been implicated in metformin action in the liver and other tissues [29,31].…”
Section: Impact Of Metformin On Reproductive Features Of Pcosmentioning
confidence: 93%
“…However, there is evidence that metformin directly inhibits ovarian steroidogenesis [33,34]. Inhibition of mitochondrial Complex I has been implicated as one potential mechanism for this action [35]. There is also evidence that metformin lowers androgen levels by an inhibitory effect on 3β-hydroxysteroid dehydrogenase/Δ 5 -Δ 4 isomerase type 2 [36].…”
Section: Mechanisms Of Metformin Action In Target Tissues Relevant Tomentioning
confidence: 99%
“…The OROBOROS oxygraph was used to measure oxygen consumption in permeabilised cells using a substrate-uncoupler-inhibitor titration regimen as previously described 21. The oxygen consumption rates were calculated and expressed as specific oxygen consumption rates (pmol O 2 /s/10 6 cells).…”
Section: Subject and Methodsmentioning
confidence: 99%
“…Thus, the concept that members of the biguanide family, including phenformin and metformin, exert many of their actions though modulation of mitochondrial energetics is not a recent proposal. During the last decade, the specific inhibition of the mitochondrial respiratory-chain complex 1 by metformin was confirmed in many cellular models, including rat, mouse and human primary hepatocytes (El-Mir et al, 2000;Owen et al, 2000;Stephenne et al, 2011), hepatoma, and adrenocortical carcinoma immortalized cell lines (Guigas et al, 2004;Hirsch et al, 2012;Kim et al, 2013), skeletal muscle homogenates (Brunmair et al, 2004), endothelial cells (Detaille et al, 2005), pancreatic beta cells (Hinke et al, 2007), neurons (El-Mir et al, 2008), peripheral blood mononuclear cells and platelets (Piel et al, 2014), and more recently in cancer cells (Bridges et al, 2014;Janzer et al, 2014;Scotland et al, 2013;Wheaton et al, 2014). It has been reported that this transient inhibition of complex 1 induces a drop in cellular energy charge, a measure of the energetic state of the cell defined as ( (Foretz et al, 2010;Stephenne et al, 2011).…”
Section: Metformin and Mitochondrial Oxidative Phosphorylationmentioning
confidence: 99%